Early antipsychotic treatment in juvenile rats elicits long-term alterations to the adult serotonin receptors - De Santis M (Neuropsychiatric Disease and Treatment, 2018)
Michael De Santis,1,2 Xu-Feng Huang,2 Chao Deng1,2 1Antipsychotic Research Laboratory, Illawarra Health and Medical Research Institute, University of Wollongong, Wollongong, NSW, Australia; 2School of Medicine, University of Wollongong, Wollongong, NSW, Australia Background: Antipsychotic drug (APD) prescription/use in children has increased significantly worldwide, despite limited insight into potential long-term effects of treatment on adult brain functioning. While initial long-term studies have uncovered alterations to behaviors following early APD treatment, further investigations into potential changes to receptor density levels of related neurotransmitter (NT) systems are required. Methods: The current investigation utilized an animal model for early APD treatment with aripiprazole, olanzapine, and risperidone in male and female juvenile rats to investigate potential long-term changes to the adult serotonin (5-HT) NT system. Levels of 5-HT1A, 5-HT2A, and 5-HT2C receptors were measured in the prefrontal cortex (PFC), caudate putamen (CPu), nucleus accumbens (NAc), and hippocampus via Western Blot and receptor autoradiography. Results: In the male cohort, long-term changes to 5-HT2A and 5-HT2C receptors were found mostly across hippocampal and cortical brain regions following early aripiprazole and olanzapine treatment, while early risperidone treatment changed 5-HT1A receptor levels in the NAc and PFC. Lesser effects were uncovered in the female cohort with aripiprazole, olanzapine and risperidone to alter 5-HT1A and 5-HT2A receptors in NAc and hippocampal brain regions, respectively. Conclusion: The results of this study suggest that early treatment of various APDs in juvenile rats may cause gender and brain regional specific changes in 5-HT2A and 5-HT2C receptors in the adult brain. Keywords: antipsychotic drug, serotonin, risperidone, olanzapine, aripiprazole, development, juvenile